Green Synthesis of Zinc Oxide Nanoparticles: Fortification for Rice Grain Yield and Nutrients Uptake Enhancement - Omnia M. Elshayb; Khaled Y. Farroh; Heba E. Amin; Ayman M. Atta (Molecules, 2021)
Applications of metal oxide nanoparticles in the agriculture sector are being extensively included as the materials are considered superior. In the present work, zinc oxide nanoparticle (ZnO NPs), with a developing fertilizer, is applied in the fortification of rice grain yield and nutrient uptake enhancement. To evaluate the role of ZnO NP, two field experiments were conducted during the 2018 and 2019 seasons. ZnO NPs were small, nearly spherical, and their sizes equal to 31.4 nm, as proved via the dynamic light scattering technique. ZnO NPs were applied as a fertilizer in different concentrations, varying between 20 and 60 mg/L as a foliar spray. The mixture of ZnSO4 and ZnO NP40 ameliorated yield component and nutrients (N, K, and Zn) uptake was enhanced compared to traditional ZnSO4 treatment. Nevertheless, the uptake of the phosphorous element (P) was adversely affected by the treatment of ZnO NPs. Thus, treatment via utilizing ZnO NPs as a foliar with a very small amount (40 ppm) with of basal ZnSO4 led to a good improvement in agronomic and physiological features; eventually, higher yield and nutrient-enriched rice grain were obtained.